Difficult Discharges to Skilled Nursing Facilities Attributed to Multiple Sclerosis Medications: An Observational Study. (April 2020) - Munger, Kathleen C.; George, Benjamin P.; Samkoff, Lawrence M.; Robb, Jessica F.
Background: The costs of multiple sclerosis (MS) disease-modifying therapies (DMTs) and certain symptomatic treatments (ie, dalfampridine [DFP]) are high. Consolidated billing models require that medication costs be covered by skilled nursing facilities (SNFs) after hospitalization. As a result, patients may experience suboptimal discharge, off of medication or without rehabilitation. Methods: To characterize the frequency with which MS pharmaceutical costs lead to suboptimal discharge, we performed a retrospective chart review of admissions to a large academic medical center from January 2013 to December 2017 among patients with MS on DMT and/or DFP with SNF rehabilitation recommendations. We quantified the burden of suboptimal discharge due to medication discontinuation, limited medication supplies, or forgone rehabilitation. Results: Among 169 admissions of patients with MS with discharge recommendations for SNF rehabilitation, there were 57 (33.7%) admissions across 49 patients with MS on DMT/DFP. Overall, 39 (68%) of 57 admissions (71% of patients) experienced a suboptimal discharge. Overall, 29 (65%) discontinued DMT/DFP, 9 (16%) took their remaining home supply of medications during rehabilitation (including 5 admissions also affected by a discontinuation), and 6 (11%) were discharged home to remain on DMT. Among those discharged to rehabilitation, discharge to a hospital-owned SNF was associated with a routine discharge with no lapse in medication (n = 11/15 vs 7/36, P < .001). Conclusions: High costs of MS medications in conjunction with SNF consolidated payment models result in misaligned incentives and often lead to medication discontinuation or other suboptimal discharge for patients with MS.